Art Collections, Private and Public: A Comparative Legal Study - Moustaira, Elina (Springer, 2015)
This book is a comparative legal study of the private and public art collections in various states of the world, covering the most important issues that usually arise and focusing on the differences and the similarities of the national laws in the treatment of those issues